1990
DOI: 10.1073/pnas.87.12.4794
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of acetylcholine-elicited currents in PC12 pheochromocytoma cells.

Abstract: The current-voltage (I-V) relationship for acetylcholine-elicited currents in the rat pheochromocytoma cell line PC12 is nonlinear. Two voltage-dependent processes that could account for the whole-cell current rectification were examined, receptor channel gating and single receptor channel permeation. We found that both factors are involved in the rectification of the whole-cell currents. The voltage dependence of channel gating determines the shape of the I-V curve at negative potentials. The single-channel I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…In contrast to muscle-type receptors where the weak inward rectification can be explained by the voltage dependence of the apparent channel closing rate (Dionne & Stevens, 1975), the mechanisms underlying the inward rectification of ACh-elicited currents in ganglion cells have not been fully elucidated. The voltage dependence of gating for ganglionic ACh receptors in excised patches appears to be relatively weak (Ifune & Steinbach, 1990b;Mathie, Colquhoun & Cull-Candy, 1990) and is not steep enough to be the sole explanation for the rectification of whole-cell ACh elicited currents. In excised patches, the single channel current-voltage relationship displays inward rectification in the presence of intracellular Mg2+ (Neuhaus & Cachelin, 1990;Ifune & Steinbach, 1990bMathie et al 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to muscle-type receptors where the weak inward rectification can be explained by the voltage dependence of the apparent channel closing rate (Dionne & Stevens, 1975), the mechanisms underlying the inward rectification of ACh-elicited currents in ganglion cells have not been fully elucidated. The voltage dependence of gating for ganglionic ACh receptors in excised patches appears to be relatively weak (Ifune & Steinbach, 1990b;Mathie, Colquhoun & Cull-Candy, 1990) and is not steep enough to be the sole explanation for the rectification of whole-cell ACh elicited currents. In excised patches, the single channel current-voltage relationship displays inward rectification in the presence of intracellular Mg2+ (Neuhaus & Cachelin, 1990;Ifune & Steinbach, 1990bMathie et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The voltage dependence of gating for ganglionic ACh receptors in excised patches appears to be relatively weak (Ifune & Steinbach, 1990b;Mathie, Colquhoun & Cull-Candy, 1990) and is not steep enough to be the sole explanation for the rectification of whole-cell ACh elicited currents. In excised patches, the single channel current-voltage relationship displays inward rectification in the presence of intracellular Mg2+ (Neuhaus & Cachelin, 1990;Ifune & Steinbach, 1990bMathie et al 1990). However, many investigators have shown that removal of divalent cations from the intracellular solution does not have a dramatic effect on the current-voltage relationship of the macroscopic ACh-elicited current (Hirano et al 1987;Mathie et al 1987;Yawo, 1989;Neuhaus & Cachelin, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition by capsaicin of ACh-activated current ACh (30 to 300 jiM) elicited a transient inward current in PC12 cells as was previously described (Ifune & Steinbach, 1990). Capsaicin (1 and 3 tM) suppressed this ACh-elicited current (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Ifune & Steinbach (1990) in PC12 cells. Capsaicin did not affect the voltage-dependence of the ACh-activated current in four out of four cells tested: the current activated in the presence of capsaicin also exhibited inward rectification and the inward component in the negative potential range was uniformly suppressed (Figure 5a).…”
Section: S2mentioning
confidence: 99%
“…This suggested that rectification is caused either by channel block by intracellular components (that are not present in artificial intracellular solutions) and/or by voltagedependence of the channel kinetics (Mathie et al, 1990). We now know that both are important: the major role is played by channel block by micromolar concentration of the intracellular polyamine, spermine (Haghighi & Cooper, 1998), with a minor contribution by intracellular magnesium ions (Mathie et al, 1990;Ifune & Steinbach, 1990;Ifune & Steinbach, 1992) and by the voltage dependence of the channel P open . While this work was carried out on native neuronal nicotinic receptors of autonomic ganglia (and on recombinant α4β2 and α3β4 channels), it is likely that similar mechanisms underlie the rectification of other neuronal nicotinic receptors (Alkondon et al, 1994).…”
Section: Inward Rectificationmentioning
confidence: 99%